ANALISIS UKURAN PERUSAHAAN, FREE CASH FLOW(FCF) DAN KEBIJAKAN HUTANG TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Bhakti Helvi Rambe (ECOBISMA (JURNAL EKONOMI, BISNIS DAN MANAJEMEN), 2020)
The purpose of this study was to analyze the Free Cash Flow (FCF) Firm Size and the Debt to Equity Ratio on Financial Performance of Manufacturing Companies on the Indonesia Stock Exchange. This research is causal. The data taken as this research are Manufacturing Companies listed on the Indonesia Stock Exchange in 2017-2018. The population in the study was 146 companies, with a sample of 30 companies using the purposive sampling method, so that the number of observations was 60 units of observation. The data analysis method in this research is multiple linear regression. R Square Testing Results of 0.162 means that the independent variable is X1Firm Size x2 Free Cash Flow (FCF), x3 Debt to Equty Ratio simultaneously affects Financial Performance by 16.2% and the remaining 83.8% is influenced by other factors. Research Results Partially understood that the Firm Size variable has no negative effect and is not significant on Financial Performance. According to the data in table 5. Results of the statistical equation test that the value of Sig. Firm Â Size variable x1 0.872> 0.05 does not affect and is not significant to the dependent variable Y Financial Performance then the hypothesis is rejected. The results of the study are partially understood that the Free Cash Flow (FCF) variable has a positive and significant effect on financial performance. According to the data in table 5. Results of the statistical equation test that the value of Sig. variable Free Cash Flow (FCF) x2 0.043 <0.05 significant effect on the dependent variable Y Financial Performance. Then the variable Free Cash Flow (FCF) hypothesis has a positive effect on the Financial Performance of Manufacturing Companies in the Indonesia Stock Exchange. The research results are partially known that the Debt to Equity Ratio variable has a positive and significant effect on Financial Performance. Sig value. Debt to Equity Ratio Variable x3 0.018 <0.05 has a significant effect on the dependent variable Y Financial Performance of manufacturing companies on the Indonesia Stock Exchange. Then the hypothesis of Debt to Equity Ratio Variables has a positive effect on the Financial Performance of Manufacturing Companies on the Indonesia Stock Exchange. It is simultaneously significant. Where the probability value (Sig.) 0.018 <0.05, the influence of the free variable consists of the variable Company Size x1, Free Cash Flow (FCF) variable x2, Debt to Equity Ratio Variable x3 Against the Bound Variable Financial Performance variable Y in Manufacturing Companies listed on Indonesia stock exchange.